2008
DOI: 10.1002/ccd.21539
|View full text |Cite
|
Sign up to set email alerts
|

Dorsalis pedis artery stenting for limb salvage

Abstract: Stent-supported angioplasty has emerged as an effective alternative to distal bypass for infrapopliteal artery disease. This treatment has been mainly employed in the tibial and peroneal arteries. However, the pedal artery below the ankle is the final frontier for catheter intervention. Here, we describe the utility of dorsalis pedis artery stenting for limb salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 119 publications
0
17
0
Order By: Relevance
“…A tapered tip coronary guide wire or 0.010‐inch guide wire was used in a case of failed 0.014‐inch guide wire crossing (two cases, 1.9%). For recanalization of chronic total occlusion (CTO) lesions in crural segments, a conventional coronary technique or a “J‐loop technique” using a 0.014‐inch guide wire was used to cross the occlusive lesion [4–7]. When a penetration technique was needed, a CTO‐dedicated 0.014‐ and/or 0.018‐inch guide wire were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A tapered tip coronary guide wire or 0.010‐inch guide wire was used in a case of failed 0.014‐inch guide wire crossing (two cases, 1.9%). For recanalization of chronic total occlusion (CTO) lesions in crural segments, a conventional coronary technique or a “J‐loop technique” using a 0.014‐inch guide wire was used to cross the occlusive lesion [4–7]. When a penetration technique was needed, a CTO‐dedicated 0.014‐ and/or 0.018‐inch guide wire were used.…”
Section: Methodsmentioning
confidence: 99%
“…With the projected increase in patients with diabetes and renal failure, infrapopliteal artery disease is a mainstay of critical limb ischemia (CLI), whether single‐segment or multisegment disease [1, 2]. During the last decade, infrapopliteal balloon angioplasty has gained significant popularity with the application of stents [3–8]. More recently, even below‐the‐ankle lesions have entered the domain of catheter‐based revascularization [7, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Macrocirculation, represented by the ankle‐brachial index (ABI) and ankle pressure, is a traditional marker for limb ischemia. Recently, aside from the macrocirculation, increasing attention has been paid to microcirculation assessment such as skin perfusion pressure (SPP) in the field of interventional limb salvage, as it relates to the probability of healing of ischemic wounds in critical limb ischemia (CLI) [1–6]. However, the association between angiographic appearance and foot circulation and linkage of macro‐ and microcirculation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…4C-E). Since Kawarada et al 11 initially reported CTO recanalization of the dorsalis pedis artery using CTO-dedicated 0.014-inch guidewires, this technique has been applied even to below-the-ankle CTOs, but it is not suitable for complex lesions, including long or calcified lesions.…”
Section: Antegrade Techniquesmentioning
confidence: 99%